2008
DOI: 10.1177/1049732308327350
|View full text |Cite
|
Sign up to set email alerts
|

Helping Direct and Indirect Victims of National Terror: Experiences of Israeli Social Workers

Abstract: In this study we explored the subjective experience and the meaning attached to it by Israeli social workers who provide help to direct and indirect victims of national terror attacks. A qualitative methodology, based on grounded theory tradition, was used to conduct and analyze interviews with 29 social workers from three types of agencies (municipal social services, general hospitals, and the National Insurance Institute) from various parts of the country. Based on the data, three main themes were constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 24 publications
5
72
1
1
Order By: Relevance
“…In contrast, several studies included in this review reported a positive association between VPTG and secondary traumatic stress (e.g., Davis & Macdonald, 2004;Kjellenberg et al, 2014). One explanation of these results may be that, prior to experiencing VPTG, individuals experience initial shock, devastation, and the shattering of their assumptions about themselves and the world (O'Sullivan & Whelan, 2011;Shamai & Ron, 2009;Splevins et al, 2010). This experience may provide the foundation for VPTG and secondary traumatic stress to develop simultaneously, contributing to the positive association reported between the two phenomena.…”
Section: Vicarious Posttraumatic Growth and Secondary Traumatic Stresscontrasting
confidence: 45%
See 4 more Smart Citations
“…In contrast, several studies included in this review reported a positive association between VPTG and secondary traumatic stress (e.g., Davis & Macdonald, 2004;Kjellenberg et al, 2014). One explanation of these results may be that, prior to experiencing VPTG, individuals experience initial shock, devastation, and the shattering of their assumptions about themselves and the world (O'Sullivan & Whelan, 2011;Shamai & Ron, 2009;Splevins et al, 2010). This experience may provide the foundation for VPTG and secondary traumatic stress to develop simultaneously, contributing to the positive association reported between the two phenomena.…”
Section: Vicarious Posttraumatic Growth and Secondary Traumatic Stresscontrasting
confidence: 45%
“…Professionals working with refugees experienced changes in their values and priorities, spiritual growth, greater personal strength, and enhanced interpersonal relationships (Barrington & ShakespeareFinch, 2013), all consistent with Tedeschi and Calhoun's (1996) conceptualisation of direct posttraumatic growth. Similar changes were noted among psychotherapists (Arnold et al, 2005), social workers (Shamai & Ron, 2009), interpreters (Splevins et al, 2010), and support workers (Guhan & Liebling-Kalifani, 2011).…”
Section: Vicarious and Direct Posttraumatic Growthmentioning
confidence: 71%
See 3 more Smart Citations